Improving Automatic Coronary Stenosis Classification Using a Hybrid Metaheuristic with Diversity Control - Miguel-Angel Gil-Rios; Ivan Cruz-Aceves; Arturo Hernandez-Aguirre; Martha-Alicia Hernandez-Gonzalez; Sergio-Eduardo Solorio-Meza (Diagnostics)
This study proposes a novel Hybrid Metaheuristic with explicit diversity control, aimed at finding an optimal feature subset by thoroughly exploring the search space to prevent premature convergence. Background/Objectives: Unlike traditional evolutionary computing techniques, which only consider the best individuals in a population, the proposed strategy also considers the worst individuals under certain conditions. In consequence, feature selection frequencies tend to be more uniform, decreasing the probability of premature convergent results and local-optima solutions. Methods: An image database containing 608 images, evenly balanced between positive and negative coronary stenosis cases, was used for experiments. A total of 473 features, including intensity, texture, and morphological types, were extracted from the image bank. A Support Vector Machine was employed to classify positive and negative stenosis cases, with Accuracy and the Jaccard Coefficient used as performance metrics. Results: The proposed strategy achieved a classification rate of <semantics>0.92</semantics> for Accuracy and <semantics>0.85</semantics> for the Jaccard Coefficient, obtaining a subset of 16 features, which represents a discrimination rate of <semantics>0.97</semantics> from the 473 initial features. Conclusions: The Hybrid Metaheuristic with explicit diversity control improved the classification performance of coronary stenosis cases compared to previous literature. Based on the achieved results, the identified feature subset demonstrates potential for use in clinical practice, particularly in decision-support information systems.